Konstruksi Perilaku Komunikasi Berbasis Nilai Metta Cittena Santi Nibbatta: Studi Fenomenologi di Yayasan Baswara Dharma Indonesia - Noviawan Rasyid Ohorella; Julio Wongtama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze how the communication of Buddhist values ​​contained in the motto Metta Cittena Santi Nibbatta is understood and applied in daily life by followers of the Baswara Dharma Indonesia Foundation and society in general. This Buddhist motto teaches the importance of sincere love in creating inner and social peace. In this study the theory used is behaviorist theory, which emphasizes the formation of behavior through the interaction between stimulus and response. This study uses a qualitative method with a descriptive approach. The paradigm used in this study is the constructivist paradigm. Data collection techniques used in the study include in-depth interviews, field observations, documentation, and literature studies. The results of the study indicate that the motto Metta Cittena Santi Nibbatta plays an important role in the communication patterns and social lives of followers of the Baswara Dharma Indonesia Foundation. The Buddhist values ​​contained in the motto create harmonious, loving, and mutually understanding interactions in daily life. With this motto, it is hoped that community life will be more compassionate and caring for one another.